ANALYSIS OF COPPER-CONTAINING PRODUCTS FOR THE CONTENT OF NOBLE METALS - Roza Ablakimovna Aubakirova; Zhanat Kairollinovna Shomanova; Ruslan Zairovich Safarov; Emin Atasoy (Academic Scientific Journal of Chemistry, 2019)
In the article we are presenting the results of electron microscopy study of the samples of blister copper taken from copper production. It was shown significant amount of noble metals – silver and gold. As a result, silver was found in the range of 0.29-0.59%, gold – up to 0.66%. The methodof assay-gravimetric detection of gold and silver in samples of blister copper is described.